Determination of antimicrobial activity of ethanolic extracts from some kinds of raw materials with tannins - Boyko, N; Zaytsev, A; Osolodchenko, T (Annals of Mechnikov's Institute, 2020)
This paper presents data about determination of antimicrobial activity of extracts from some kinds of raw materials (13 plants) with tannins. It was determined some kinds of technological parameters of extracts (concentration of total solids and density). A simple to use valuation method of antimicrobial properties of extracts – well method has been suggested and applied; for quantitative estimation of antimicrobial activity of extracts and compare them with each other, special mathematic method (vector algebra theory) has been applied. It was determined parameters of antimicrobial properties of extracts: a complex indicator of medication antimicrobial activity for quantitative estimation of antimicrobial effect - A, and correlation coefficient - r (degree of similarity to the standard), which demonstrate the spectrum of antimicrobial activity of medication. It has been selected the most promising extracts that have the medium antimicrobial activity, which obtained from the root of bergenia crassifolia А=1.89; the root of potentilla erecta А=1.92; the bark of corylus avellana А=1.76; the leaf of cotinus coggygria А=2.21. Low level of antimicrobial activity has been demonstrated by the extract obtained from the cone of alnus incana А=0.78, r=0.58. It is noted antimicrobial properties of the solutions of tannin and gallic acids 0.5% m / m in 70% vol. ethanol, that showed respectively moderate and low strength antimicrobial properties: А=1.65, r=0.99 and А=1.26, r=0.91. This potentially allows to predict the antimicrobial properties of extracts from plants containing derivatives of tannin and gallic acids on their concentration in them. It has been shown in general that raw materials that contain different kinds of tannins have possibility to use in complex phytochemical medications as antimicrobial component.